Discussion on the deployment solution of comprehensive traffic management - Yizhi DING; Hongwei LV; Yingxia NIU; Shaoping LI (Dianxin kexue)
Traffic management have been proposed for many years，operators have done a lot of pilot projects and make traffic management platform.Deepen the promotion of traffic management from scale to value is imperative.Typical business scenes of traffic management were analyzed，and the deployment solution of comprehensive traffic management was proposed.The solution was mainly composed of traffic growth in the value of the solution，the system architecture and implementation steps，including the key technology and process.Application and practice results show that this scheme can effectively stimulate the growth of traffic value.